If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(x) = 7x + -3xfind(-2) Multiply F * x xF = 7x + -3xfind(-2) Reorder the terms for easier multiplication: xF = 7x + -3 * -2dfinx Multiply -3 * -2 xF = 7x + 6dfinx Reorder the terms: xF = 6dfinx + 7x Solving xF = 6dfinx + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6dfinx' to each side of the equation. -6dfinx + xF = 6dfinx + -6dfinx + 7x Combine like terms: 6dfinx + -6dfinx = 0 -6dfinx + xF = 0 + 7x -6dfinx + xF = 7x Add '-7x' to each side of the equation. -6dfinx + -7x + xF = 7x + -7x Combine like terms: 7x + -7x = 0 -6dfinx + -7x + xF = 0 Factor out the Greatest Common Factor (GCF), 'x'. x(-6dfin + -7 + F) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-6dfin + -7 + F)' equal to zero and attempt to solve: Simplifying -6dfin + -7 + F = 0 Reorder the terms: -7 + F + -6dfin = 0 Solving -7 + F + -6dfin = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + F + 7 + -6dfin = 0 + 7 Reorder the terms: -7 + 7 + F + -6dfin = 0 + 7 Combine like terms: -7 + 7 = 0 0 + F + -6dfin = 0 + 7 F + -6dfin = 0 + 7 Combine like terms: 0 + 7 = 7 F + -6dfin = 7 Add '-1F' to each side of the equation. F + -1F + -6dfin = 7 + -1F Combine like terms: F + -1F = 0 0 + -6dfin = 7 + -1F -6dfin = 7 + -1F Add '6dfin' to each side of the equation. -6dfin + 6dfin = 7 + -1F + 6dfin Combine like terms: -6dfin + 6dfin = 0 0 = 7 + -1F + 6dfin Simplifying 0 = 7 + -1F + 6dfin The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| 2x+11=100 | | 7-5x=x | | F(x)=7x-3x | | x+7=7x-17 | | 6x+2-3x=1 | | a+b^3= | | a/4=8=13 | | 2x/0.2-x=7.03 | | (x/2)-(x/5) | | 4x-12=10x | | 2(x+3)-11=x+5 | | 4x3/8 | | 2x+14=3x+2 | | t=2t-3(1-t) | | 4x+28=2x-1 | | a(1-x)=2ax+3-2a | | 4x-28=5x-40 | | 2(3x-5)+7=33 | | 3w-4=17 | | log16x=5/2 | | ax=a-b+bx | | -5(x-2)=40 | | -2x=1/7 | | 3u-1=14 | | 4x^3+2x^2+(-8x)+3=0 | | C=7n+2(n-1) | | -4(-3w+v)+4(-6v+6w)= | | 10-4t=-2 | | s+14=31 | | X/8-2.1=-14.9 | | -7x+5=3(x-5) | | (x+1)(3x+1)=5 |